Identifying environmental factors affecting students' bullying in school: mixed analysis approach - Majid Dadashzadeh; Ali Eghbali; Shahla Khodakarimi (مطالعات روانشناسی تربیتی)
This research was conducted with the aim of identifying the environmental factors affecting the bullying of students in school, and with the mixed analysis method of exploratory type (qualitative-quantitative). The qualitative part was carried out with a grounded theory approach and a systematic method. The population includes all sixth grade teachers and school executive officers in the academic year of 1402-1403 and the sample size was determined to the point of saturation of opinions, 12 people. And it was selected with a purposeful and judgmental method (and the qualitative data was analyzed by systematic coding and by MAXQDA2020 software. Qualitative results showed 9 categories of "Lack of proper training, lack of support and communication atmosphere, informal power structure, lack of specialized dealing with bullying, character development of bully and victim, personality destruction of the bully, human factors, physical characteristics of the school, and the structure and organization of the school", are environmental factors affecting bullying. The research method in the quantitative part was descriptive-correlation and the population consisted of 1117 male students of the sixth grade of Khoy city in the academic year of 1402-1403. The sample size was determined by the Karjesi-Morgan table, 373 people, and selected using the one-stage cluster method. Data collection was done with the Illinois Bullying Questionnaire and the questionnaire of environmental factors affecting bullying among students. Analysis showed that the determined factors, directly and indirectly, are able to predict bullying in school and explain 70.9% of its variance. Based on the results, it can be said that this study has added more richness to the existing knowledge about bullying in schools, and by controlling the factors identified in this study, such as creating a supportive atmosphere and paying attention to The physical characteristics of the school reduced the amount of bullying among students.